Mechanical properties and environmental impact assessments of GFRP rebar reinforced limestone calcinated clay cement (LC3) concrete - Wang, Peng; Lai, Hongyu; Li, Wanye; Ke, Linyuwen; Wu, Haoliang; Li, Weiwen; Leung, Christopher K.Y. (Construction & building materials, 2025)
To address global greenhouse emissions, the adoption of green concrete materials has surged, aiming to lower CO₂ emissions and energy use over their lifecycle. This study comprehensively investigates the time-dependent degradation of glass fiber reinforced polymer (GFRP) rebars embedded in limestone calcined clay cement (LC3) concrete under exposure to water baths at temperatures of 23, 40 and 60 °C for up to 270 days. Both macroscopic mechanical testing (compressive strength of concrete, tensile test, flexural test and inter-laminar shear test of GFRP rebar, and pull-out test of GFRP-concrete) and environmental impact assessment are conducted to gain deeper insights. The experimental findings indicate that, when compared to normal concrete (NC), LC3 exhibits reduced aggressiveness towards the embedded GFRP rebars due to its lower alkaline content. Nonetheless, GFRP rebars still experience fiber corrosion, matrix cracking, and fiber-matrix debonding as a result of an alkaline attack from LC3. It is observed that GFRP rebar embedded in LC3 exhibit notable characteristics: an enhanced retention of tensile strength, escalating from 71.4 % to 93.3 % concerning the initial value, a similar retention in flexural and inter-laminar shear strength, and elevated ultimate bond strength from 1.83 % to 20.75 % at the GFRP-concrete interface relative to NC counterpart under identical environmental conditions. Further, these phenomena are explained by the micromorphology of aged GFRP rebars. Environmental impact assessment results show that compared with GFRP-NC, the proposed GFRP-LC3 has a lower impact on the environment, with a reduction of 20.27 % and 34.53 % for energy consumption and CO2 emissions, respectively. Considering the long-term mechanical properties and environmental impacts after degradation, GFRP-LC3 provides an effective approach for the sustainable development of construction. •GFRP-LC3 shows higher tensile and bond strength retentions than NC specimens.•GFRP-LC3 exhibits similar flexural strength and ILSS retentions as NC samples.•The deterioration mechanism of GFRP in NC and LC3 concrete is analyzed in detail.•GFRP-LC3 has a lower environmental impact compared to that of NC.•GFRP-LC3 offers an effective approach for sustainable development of construction.